Joint effects of salinity and the antidepressant sertraline on the estuarine decapod Carcinus maenas - Rodrigues, Aurélie Pinto (2015)
Concurrent exposure of estuarine organisms to man-made and natural stressors has become a common occurrence. Numerous interactions of multiple stressors causing synergistic or antagonistic effects have been described. However, limited information is available on combined effects of emerging pharmaceuticals and natural stressors. This study investigated the joint effects of the antidepressant sertraline and salinity on Carcinus maenas. To improve knowledge about interactive effects and potential vulnerability,experiments were performed with organisms from two estuaries with differing histories of exposure to environmental contamination. Biomarkers related to mode of action of sertraline were employed to assess effects of environmentally realistic concentrations of sertraline at two salinity levels. Synergism and antagonism were identified for biomarkers of cholinergic neurotransmission, energy production,anti-oxidant defences and oxidative damage. Different interactions were found for the two study sites highlighting the need to account for differences in tolerance of local ecological receptors in risk evaluations.